Ethnobotanical and ethnopharmacological study of medicinal plants used in the treatment of anemia in the region of Haouz-Rehamna (Morocco) - Ouafae Benkhnigue; Noureddine Chaachouay; Hamid Khamar; Fatiha El Azzouzi; Allal Douira; Lahcen Zidane (GarVal Editorial Ltda., 2022)
Context: The ethnobotanical study of the plants used is of great interest in the medical field. In this perspective, we have carried out this ethnobotanical and ethnopharmacological study, which is part of the development of plant resources traditionally used against anemia in a large region of Middle Atlantic Morocco (Mam-4): Al Haouz-Rehamna. Aims: To establish a catalog of medicinal plants used in traditional medicine against anemia disease. Methods: For this purpose, we carried out an ethnobotanical survey using 1700 questionnaire cards during five campaigns (from 2012 to 2017) in the studied field. In addition, the information sought was about the plant including its local name, its part used, its toxicity and, medical practices related. Ethnobotanical indices, such as Use Value (UV), Family Use Value (FUV) and, Plant Part Value (PPV), were determined. Results: The results allowed us to identify 48 medicinal plants of which 12 were toxic. The inventoried species were distributed in 45 genera and belong to 27 botanical families, of which four predominated in the number of species: Apiaceae, Amaranthaceae, Fabaceae, and Asteraceae. Also, 11 species were traditionally more used as effective plants against anemia: Rubia peregrina, Lens culinaris, Malva sylvestris, Beta vulgaris, Spinacia oleracea, Mercurialis annua, Hibiscus sabdariffa, Corrigiola telephiifolia, Nasturtium officinale, Cistus laurifolius and Armeria mauritanica. The leafy stems were the most used part (PPV = 0.28%) followed by the seed (PPV = 0.26%). These parts were usually used steamed, decocted, and rarely triturated in honey or infused in water. The recipes were administered orally until cured. Conclusions: The present study established the importance of documenting traditional knowledge about the species of medicinal plants that are used to correct many chronic diseases such as anemia. Analysis of this knowledge has shown that several of the listed plants promoted anti-anemia activity and could become the basis for in-depth scientific investigations.